Acidified diet is not effective in preventing hypocalcemia in dairy cows on French commercial farms - Aubineau, Thomas; Boudon, Anne; Guatteo, Raphaël (Frontiers in Animal Science, 2022)
The objective of this study was to assess, in the context of typical dairy farms in western France, the preventive effects of prepartum diet acidification (AcD) and mineral intake during late gestation on the incidence of subclinical hypocalcemia (calcium < 2.0 mmol/l, SHC) and subclinical hypophosphatemia (inorganic phosphorus < 1.3 mmol/l, SHP) after calving. We conducted a longitudinal study that followed a cohort of 371 Holstein cows from 26 French dairy farms; of these, 235 cows (15 farms) were supplied with anionic salts during late gestation, and 136 cows (11 farms) were not. Blood samples were collected from 1 to 22 cows per farm (average of 14.3 cows per farm) between 24 and 48 h after calving. Total calcium and inorganic phosphorus concentrations in plasma were then quantified by inductively coupled plasma - optical emission spectrometry. The effects of AcD on the incidence of SHC and SHP were assessed using mixed linear models that evaluated the cow-level factors parity, milk yield index, and individual health events/treatments, and the farm-level factors diet calcium and magnesium content, dietary phosphorus intake, vitamin D supply, diet crude protein content, and duration of AcD, with farm as a random effect. Approximately 55% of cows were diagnosed with SHC (n = 203) and 37% with SHP (n=136). The first model confirmed earlier findings that the risk of SHC is higher with increased parity (P ≤ 0.0001) and revealed a higher risk associated with high milk yield (P = 0.0005), high phosphorus intake (40–60 g/cow per day, OR = 3.5; ≥ 60 g/cow per day, OR = 7.3; P = 0.0003) and high vitamin D supply (≥ 19950 IU/cow per day, OR = 3, P = 0.007). The second model highlighted a greater risk of SHP with increasing parity (P = 0.03) and showed trends for the preventive effects of AcD (OR = 0.4, P = 0.07) and moderate amounts of phosphorus in the diet (OR = 0.4, P = 0.10). Overall, our results do not support the effectiveness of AcD in preventing SHC or SHP under field conditions examined here, probably resulting from insufficient diet acidification.